Dynamics of Change in Kerala's Education System: The Socio-economic and Political Dimensions - K.K.George Parvathy Sunaina (CSESWP12, 2005)
This paper attempts to situate the dynamics of change in the educational sector of Kerala in the broad context of the dynamics of its economy, society and polity. It deals with the political and social forces, which have been impacting upon the State's educational system. The paper begins with a brief overview of the developments in the State's education, its distinguishing characteristics and the major issues, whichhave cropped up in recent years. It discusses some aspects of Kerala economy and society, which have a direct influence on the State's education system. Growth in State Domestic Product, structural changes in the economy, growth in employment and unemployment, international migration, demographic changes and State's fiscal crisis are some of the areas covered under this head. The paper also examines the trends in the educational finances of the State. The paper finds that the share of education in the State's budget has reached an all-time low precisely when the State Domestic Product has been recording all-time high growth rates. The vacuum created by the withdrawal of the State is now being filled by unaided selffinancing institutions, especially in the professional educational sector. There is a paradigm shift in the State's education from an all-inclusive system, attempting to reach education to all social and economic groups, to an exclusive system, limiting access to the upper echelons of society. The pendulum seems to be swinging from one extreme to the other, from a highly subsidized and state sponsored system to a total student financing system. This shift in approach has the potential of undermining the very Kerala Model of Development and is likely to have far-reaching adverse social and economic consequences